Islamic Bibliotherapy for Mental Health: A Systematic Review of Qur'anic Text-Based Interventions - Susanti, Rizky (Universitas Muhammadiyah Surakarta, 2025)
Mental health challenges are increasing globally, including in Muslim communities, where conventional psychological approaches often overlook spiritual and existential aspects of healing. Bibliotherapy-a method using selected reading materials such as stories, poetry, or scripture to facilitate emotional expression, cognitive restructuring, and meaning-making-when grounded in Islamic tradition becomes Islamic bibliotherapy: a psychospiritual intervention utilizing Qur'anic verses, prophetic stories, prayers, Islamic metaphors, thematic ayat, and Islamic literature to foster peace, resilience, and spiritual growth.This study presents a Systematic Literature Review (SLR) synthesizing empirical and conceptual works on Islamic bibliotherapy for mental health, following PRISMA 2020 guidelines. Thirteen studies-comprising experimental and qualitative research, conceptual analyses, bibliometric mapping, and scoping reviews-were analyzed to identify approaches, Islamic texts used, target populations and contexts, psychological–spiritual outcomes, and research gaps.Findings show that Islamic bibliotherapy enhances spiritual coping, emotional regulation, and narrative healing through reflective reading of QS Maryam and QS Al-Insyirah, metaphor-based counseling, narrative integration of Prophet Ayyub's story, and dissemination of Islamic fiction. Despite positive outcomes-reduced anxiety, increased hope, and strengthened resilience-most studies lack standardized protocols and spiritually sensitive tools. Islamic bibliotherapy holds strong potential as a culturally grounded, spiritually enriched modality, yet requires methodological refinement and broader application.